Exogenous application of GA3 influences morphological traits and developmental transitions in Or gene introgressed Indian cauliflower (Brassica oleracea var. botrytis) - CHANDEL, ANAMIKA; SINGH, SHRAWAN; MANGAL, MANISHA; TOMAR, B S; NAGAR, SHIVANI; BOLLINEDI, HARITHA; SHIVRAN, BHAG CHAND; SAGAR, SUSHMA (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during the winter (rabi) season of 2021–22 and 2022–23 at ICAR-Indian Agricultural Research Institute, New Delhi aimed to study the impact of GA3 spray on morphological traits and developmental transitions in Or gene introgressed CFOr (PKVA-1HM) and white CFWT (DC 18–19) genotypes of Indian cauliflower (Brassica oleracea var. botrytis L). Total of 24 treatment combinations comprising four GA3 concentrations, viz. Go, Control; G1, 250 ppm; G2, 500 ppm and G3, 1000 ppm; two genotypes, CFOr (homozygous orange) and CFWT (white); three applications at different plant stages, viz. S1, Vegetative stage (VS); S2, VS + curd initiation stage (CIS) and S3, VS + CIS + full curd stage (FCS) in factorial randomised block design (Factorial- RBD) with three replications. Observations were recorded for six morphological traits and five developmental transitions. Significant differences were found for all three factors, viz. GA3 concentration, genotypes and plant stages. A spray of 500 ppm GA3 on CFOr and CFWT genotype at VS + CIS stage resulted in superior performance in morphological traits and developmental transitions. It resulted maximum stalk length (69.33 cm) in CFOr, however, it was statistically similar to 250 ppm GA3 spray at VS + CIS stage in CFWT (69.83cm). Both levels resulted in synchronization in flowering time of CFOr (153 days) and CFWT (153.5 days). The findings highlight the role of GA3 application in CFOr and CFWT genotypes for improving morphological traits and synchronize flowering for hybrid seed production.